The Accounts receivable turnover - Fauzi Achmad Fauzi (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2020)
The strategy for controlling the accounts receivable turnover is very important, because it affects the provision of credit. The slower the circulation of receivables, the more uncollected receivables, this will lead to bad credit / problem loans. Each company has an effort to overcome the circulation of receivables so that they do not experience a large number of problem loans / NPLs. The effort that PT. Bank XDC (Persero) Tbk, to increase receivables turnover is an analysis of accounts receivable turnover rates. The research method is qualitative method, while the method of data collection is using the method of observation, interviews, library studies. Receivables turnover at PT. Bank XDC (Persero) Tbk, has increased every year well. This is due to the higher receivables turnover and the lower average collection time for receivables. The increase in receivables turnover greatly affects the level of problem loans. The higher the rate of turnover of receivables, the better the level of problem loans / NPLs. Keyword: Receivable round, Non-Performing Loans